Electromagnetism and the metonymic imagination - Murphy, Kieran M. (Kieran Marcellin), 1977- (AnthropoScene., 2020)
"Illustrates how the discovery of electromagnetism in 1820 not only led to technological inventions, such as the dynamo and the telegraph, but also legitimized modes of reasoning that manifested a sharper ability to perceive how metonymic relations could reveal the order of things"--